2018
DOI: 10.2340/16501977-2362
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of the Life Satisfaction Questionnaire (LiSat-11) and association between items in individuals with chronic stroke

Abstract: LiSat-11 is considered reliable and can be recommended for assessing life satisfaction after stroke. The association between items indicates that LiSat-11 measures various aspects that can impact on an individual's life satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 27 publications
4
24
2
Order By: Relevance
“…However, the systematic and random variations were small and nonsignificant. The results differ somewhat from those of the stroke study, 26 where more items (7 of 11) showed positive systematic disagreements but no significant systematic or random disagreements, except for "Partner relationship" (ie, a small negative change in RP). Thus, some random variation might be expected when using LiSat-11 in these populations.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…However, the systematic and random variations were small and nonsignificant. The results differ somewhat from those of the stroke study, 26 where more items (7 of 11) showed positive systematic disagreements but no significant systematic or random disagreements, except for "Partner relationship" (ie, a small negative change in RP). Thus, some random variation might be expected when using LiSat-11 in these populations.…”
Section: Discussioncontrasting
confidence: 94%
“…This is in line with the previous study in persons with chronic stroke that reported similar Kappa coefficients (0.59-0.97) and high percent agreement (PA ≤ 1 > 89%). 26 In the present study, most items showed negative systematic disagreements, indicating that the participants systematically rated lower scores at T2. However, the systematic and random variations were small and nonsignificant.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Data on experienced life satisfaction were collected using the Life Satisfaction Checklist (LiSat-11) (9). The questionnaire is commonly used to assess life satisfaction after stroke and has been found to be reliable (17). It is a self-report generic questionnaire that assesses life satisfaction with the global item "Life as a whole" and 10 domain-specific items.…”
Section: Data Collectionmentioning
confidence: 99%